Local and systemic effects caused by Crotalus durissus terrificus, Crotalus durissus collilineatus, and Crotalus durissus cascavella snake venoms in swiss mice - Carvalho, Letícia Helena De; Teixeira, Leda Fabiélen; Zaqueo, Kayena Delaix; Bastos, Jéssica Felix; Nery, Neriane Monteiro; Setúbal, Sulamita Silva; Pontes, Adriana Silva; Butzke, Diana; Cavalcante, Walter; Gallacci, Marcia; Fernandes, Carla Freire Celedônio; Stabeli, Rodrigo Guerino; et al. (Sociedade Brasileira de Medicina Tropical - SBMT, 2019)
AbstractINTRODUCTION: Crotalus envenomations cause serious complications and can be fatal without appropriate treatment. Venom isoforms present and inter/intraspecific variations in the venom composition can result in different symptoms presented by bites by snakes from the same species but from different geographical regions. We comparatively evaluated the local and systemic effects caused by Crotalus durissus terrificus (Cdt), C.d. collilineatus (Cdcolli), and C.d. cascavella (Cdcasc) envenomation.METHODS:Venom chromatography was performed. Proteolytic, phospholipase, and LAAO activities were analyzed. Edema, myotoxicity, hepatotoxicity, nephrotoxicity, and coagulation alterations were evaluated.RESULTS:The venom SDS-PAGE analyses found the presence of convulxin, gyroxin, crotoxin, and crotamine in Cdt and Cdcolli venoms. Crotamine was not present in the Cdcasc venom. Cdt, Cdcollli, and Cdcasc venoms had no proteolytic activity. Only Cdcasc and Cdt venoms had phospholipase activity. LAAO activity was observed in Cdcolli and Cdcasc venoms. Cdcolli and Cdcasc venoms caused 36.7% and 13.3% edema increases, respectively. Cdt venom caused a 10% edema induction compared to those by other venoms. All venoms increased TOTAL-CK, MB-CK, and LDH levels (indicating muscle injury) and ALT, AST, GGT, and ALP levels (markers of liver damage) and were able to induce a neuromuscular blockade. Urea and creatinine levels were also altered in both plasma and urine, indicating kidney damage. Only Cdcolli and Cdcasc venoms increased TAPP and TAP.CONCLUSIONS:Together, these results allow us to draw a distinction between local and systemic effects caused by Crotalus subspecies, highlighting the clinical and biochemical effects produced by their respective venoms.
Keywords: Crotalus durissus; Myotoxicity; Nephrotoxicity; Hepatotoxicity; Neurotoxicity; Edema